1998
DOI: 10.1149/1.1838753
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of  CO 2 and NaCl on the Atmospheric Corrosion of Zinc: A Laboratory Study

Abstract: We report on a laboratory study of the atmospheric corrosion of NaC1-treated zinc in air containing different concentrations of carbon dioxide (<1, 100, 350, 1000, and 40,000 ppm). Each sample was exposed individually to synthetic atmospheres with careful control of CO2 concentration and flow conditions. The relative humidity was 95%. The protective properties of carbonate-containing corrosion products were investigated in 225 ppb SO2. Mass gain and metal loss results are reported. The corrosion products were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 3 publications
7
58
0
1
Order By: Relevance
“…At low CO 2 concentrations, ZnO was the main corrosion product. These results agree with investigations made on open surfaces [10,11], where it was found that the corrosion rate was considerably higher at low CO 2 concentrations (< 1 ppm) than it was at the ambient concentration of 350 ppm. The effect was explained by neutralisation of the surface electrolyte at the cathodic sites and the precipitation of less soluble zinc hydroxychloride.…”
Section: Introductionsupporting
confidence: 92%
“…At low CO 2 concentrations, ZnO was the main corrosion product. These results agree with investigations made on open surfaces [10,11], where it was found that the corrosion rate was considerably higher at low CO 2 concentrations (< 1 ppm) than it was at the ambient concentration of 350 ppm. The effect was explained by neutralisation of the surface electrolyte at the cathodic sites and the precipitation of less soluble zinc hydroxychloride.…”
Section: Introductionsupporting
confidence: 92%
“…EDX analysis indicates the presence of high concentration of Zn, Cl, O, and small amount of Sn in the layer. Combining the EDX results in this work and those in the literature [18,[28][29][30], it is deduced that these corrosion products were mixtures of zinc hydroxychloride (simonkolleite, Zn 5 (OH) 8 Cl 2Á H 2 O) and ZnO/Zn-(OH) 2 , probably with some tin hydroxychloride. The dominant composition of zinc of the corrosion products also suggests that pitting attack of the alloy is intimately connected with local selective dissolution of zinc within the microstructure.…”
Section: Cross-sectional Characterization Of Corrosion Productssupporting
confidence: 74%
“…In the presence of chloride ions, especially when the chloride concentration is higher than 0.01 M, Cl À will move towards the zinc dissolution sites, where the insoluble zinc hydroxychloride (simonkolleite), Zn 5 (OH) 8 Cl 2 zH 2 O, may form gradually [28]:…”
Section: Corrosion Mechanism Of Sn-zn Alloys In Chloridecontaining Somentioning
confidence: 99%
“…The minerals that form are functions of the gas phase composition, in particular CO 2 , and the aqueous solution composition. As expected the corrosion products that form are a function of chloride and sulfate content of the aqueous solutions (Falk et al, 1998;Blucher et al, 2003;Linstrom et al, 2004). The net effects of these precipitation reactions at the cathodic sites are inhibition of oxygen reduction reaction by blocking of sites and the loss of water due to removal of aqueous ionic species due to mineral precipitation.…”
Section: Chemical Transformations In Thin Films On Alloy 22mentioning
confidence: 52%